Neural Circuitry Underlying Waking Up to Hypercapnia - Kaur, Satvinder; Saper, Clifford B. (Frontiers in Neuroscience, 2019)
Obstructive sleep apnea is a sleep-related breathing disorder, in which, patients suffer from cycles of atonia of airway dilator muscles during sleep, resulting in airway collapse, followed by brief arousals that restore airway patency. These repeated arousals which can occur hundreds of times during the course of a night, result in sleep disruption, which in turn causes cognitive impairment as well as cardiovascular and metabolic morbidities. Preventing arousal from sleep while preserving the increase in respiratory drive that reinitiates breathing could potentially prevent this outcome, but will require understanding the circuits that mediate both the cortical and respiratory responses to apnea. The parabrachial nucleus (PB) is located in rostral pons. It receives chemosensory information from medullary nuclei that sense increase in CO2 (hypercapnia), decrease in O2 (hypoxia) and mechanosensory inputs from airway negative pressure during apneas. The PB area also exerts powerful control over cortical arousal and respiration, and therefore, is an excellent candidate for mediating the EEG arousal and restoration of the airway during sleep apneas. Using various genetic tools, we dissected the neuronal sub-types responsible for relaying the stimulus for cortical arousal to forebrain arousal circuits. The present review will focus on the circuitries that regulate waking-up from sleep in response to hypercapnia.